REPRESENTATIVE POTENTIAL OF DESIGNER PRACTICES IN SYMBIOSIS OF ART AND FASHION - Лагода, О. М. (Art and Design, 2018)
Determination of representatives interaction of contemporary art and designers of clothing with regard to the shaping of a fashionable costume and its representations. An overview of scientific sources highlighting the interaction of art and fashion; comparative analysis of the ways of such interaction in different formats of representations; axiological approach to the analysis of existing original models of cooperation between artists and designers; the definition of ways to apply works of contemporary art in the framework of design practices that are manifested in the search for shape formation and in the decorative solution.